Strategi Komunikasi Pemasaran Melalui Media Instagram @serambibotaniofficial untuk Meningkatkan Penjualan - Lismayani, Tiara Dwi; Nina Kusumawati (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to analyze the marketing communication strategy through the Instagram account @serambibotaniofficial in building consumer engagement and its influence on sales, particularly at Serambi Botani’s physical store. A descriptive qualitative method was applied, with data collected through in-depth interviews, observation, and documentation. The study uses the Marketing Mix (4P) framework, consisting of product, price, place, and promotion. The findings reveal that Serambi Botani leverages Instagram to build brand awareness and strengthen relationships with consumers through educational content, consistent visuals, and a soft selling approach. Products are presented informatively, prices are communicated through seasonal promotions, distribution is directed to both offline and online channels, and promotion is carried out through a mix of educational posts, testimonials, and simple interactions. Although the strategy has not significantly boosted direct sales, it has proven effective in shaping a positive brand image, expanding audience reach, and maintaining consumer relationships. Optimizing interactive features such as reels, live, and Q&A is recommended to enhance audience engagement and potential sales conversions in the future.